y的四次方-y² 3ax²-3ay² 4x³-8x²+4xy的四次方-y² 3ax²-3ay² 4x³-8x²+4x a²-2a(b+c)+(b+c)²

来源:学生作业帮助网 编辑:作业帮 时间:2017/12/14 12:15:54
y的四次方-y²3ax²-3ay²4x³-8x²+4xy的四次方-y²3ax²-3ay²4x³-8x²

y的四次方-y² 3ax²-3ay² 4x³-8x²+4xy的四次方-y² 3ax²-3ay² 4x³-8x²+4x a²-2a(b+c)+(b+c)²
y的四次方-y² 3ax²-3ay² 4x³-8x²+4x
y的四次方-y² 3ax²-3ay² 4x³-8x²+4x a²-2a(b+c)+(b+c)²

y的四次方-y² 3ax²-3ay² 4x³-8x²+4xy的四次方-y² 3ax²-3ay² 4x³-8x²+4x a²-2a(b+c)+(b+c)²
(1)y的四次方-y²
y²(y²-1)
=y²(y-1)(y+1)
(2)3ax²-3ay²
3a(x²-y²)
=3a(x-y)(x+y)
(3)4x³-8x²+4x
4x(x²-2x+1)
=4x(x-1)²
(4)a²-2a(b+c)+(b+c)²
{a-(b+c)}²
=(a-b-c)²

y^4-y^2
=y^2(y^2-1)
=y^2(y+1)(y-1)

3ax^2-3ay^2
=3a(x^2-y^2)
=3a(x+y)(x-y)

4x^3-8x^2+4x
=4x(x^2-2x+1)
=4x(x-1)^2

a^2-2a(b+c)+(b+c)^2
=[a-(b+c)]^2
=(a-b-c)^2